Organisational factors enhancing the use of information technology for knowledge management: a study in Malaysian listed organisations - Aman, Fadhilah (Curtin University, 2010)
Managing knowledge appears to be key in improving organisations’ competencies in the face of global competition. In the case of Malaysian organisations, extant studies revealed a disparity between perceived importance of information technology (IT) and its actual utilisation to support knowledge management (KM). In order to achieve a knowledge-based economy, Malaysian organisations need to embrace the use of IT to support their KM initiatives to ensure that knowledge is diffused and applied in the best possible way to support further innovation and drive economic growth. Hence, the acceptance and use of IT in Malaysian KM is of paramount concern.This research addressed this issue by examining IT utilisation by Malaysian organisations to support KM. Research has shown that failures in deploying ITbased systems to support KM are in part attributed to the inadequate attention to other factors, such as structures, processes, and culture of an organisation. Thus, the main objective of this study was to understand the key organisational factors enhancing the use of IT to support KM in the Malaysian listed organisations. Furthermore, most of the studies on IT use for KM were conducted in the Western context. The current research was conducted in the Malaysian context, using a model that accounted for key variables, the relevancy and appropriateness of such in the particular context being verified in the preliminary investigation phase of the research.The technology acceptance model (TAM) provides the theoretical framework for this study’s investigation. In addition to the two major constructs of perceived usefulness and perceived ease of use in TAM, six variables of organisational factors, garnered from a review of relevant literature and validated by a series of interviews in Malaysian listed organisations—including management support and commitment, knowledge sharing culture, rewards and incentives, knowledge classification, and policies and procedures of using IT for KM—were incorporated in the research model proposed for this study. Based on the findings from the preliminary investigation phase, another organisational factor was identified, namely, having appropriate KM processes to manage knowledge in an organisation, and thus was added to the refined research model. A survey was conducted among 830 IT and KM managers from the Malaysian listed organisations to collect quantitative data. The data collected were analysed using the structural equation modelling (SEM) approach with partial least squares (PLS) technique to test the hypotheses developed and assess the research model.The major findings of this research have confirmed the influence of KM processes, knowledge classification, knowledge sharing culture, and perceived benefits of using IT for KM as the major determinants of IT use to support KM in the organisations studied. However, the positive effects of rewards and incentives, policies and procedures of using IT for KM, and perceived ease of use, on the extent of IT use for KM were not detected. Furthermore, the results demonstrated the effect of management support and commitment on the use of IT for KM was only indirect through its mediation on knowledge classification and knowledge sharing culture. The results also suggested that the research model explained almost two-thirds (65.6%) of the variance in IT use for KM.This research provides significant and original contributions to the existing knowledge in the acceptance and use of IT to support KM area. The unique theoretical contributions of this study include the demonstration of an extension of the TAM to investigate the influence of organisational factors on the extent of IT use to support KM, in particular, in the context of Malaysian organisations. The results of the study have important practical and theoretical implications for employers, governments, information system professionals and information system researchers. Most importantly, an understanding of the organisational factors enhancing the extent of IT use for KM provides guidelines for the Malaysian organisations in developing better KM and IT strategies in order to promote and encourage the use of IT to support the organisations’ KM initiatives.